Upholding Islamic business ethics: Enhancing passenger service satisfaction in bus transportation - Fauzi, Qudsi; Ulfah, Ulfah; Wijayanti, Ida; Wardhana , Akhmad Kusuma; Niroula, Ballav (al-Uqud : Journal of Islamic Economics, 2024)
Islamic business principles are applicable to traders, ensuring that sales are not merely for profit as a secular objective, but also to attain blessings from Allah SWT. This research seeks to elucidate the Islamic business ethics implemented in a transportation enterprise and their effects on passenger satisfaction. This research employed case study and descriptive exploratory analytic methodologies. Data gathering was conducted through comprehensive interviews. Consequently, data validation is achieved through data triangulation. The findings indicate that bus crews applied four principles of Islamic business ethics. Simultaneously, the principles of honesty (Siddiq) and transparency (tabligh) are not comprehensively adhered to by the bus crew employed by this company. They performed well in terms of duty (amanah) and professionalism (fathonah). The application of Islamic ethics in bus services influences customer pleasure. This research offers numerous practical implications for professionals in the transportation industry.